Majesty and music in royal worship: the English Chapel Royal, 1558–1625 - Patton, O (Cambridge University Press, 2025)
This article revises interpretations of the post-Reformation English Chapel Royal as a place for the performance of ‘conservative’ or ‘traditional’ forms of the Book of Common Prayer and establishes its importance as a space for negotiating Protestant royal worship. By detailed analysis of the sound and appearance of royal chapels under Elizabeth and James, the Chapel Royal is emphasised not for its anticipation of a Laudian ascendancy, but its sensitivity to the ceremonial boundaries of the reformed Church of England, and ability to negotiate a form of Protestant majesty in royal worship.